PERANCANGAN DAN EVALUASI SISTEM LOSIDA (LODONG SISA DAPUR) UNTUK PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA: Evaluasi Sistem pengelolaan sampah organik (metode LOSIDA) - Arbiatun, Fatimah; Mirino, Tracey Precilia; Wulandari, Annisa Ayuningtyas; Sasim, Desilvi Ayu Tari (LRI Universitas Muhammadiyah Sorong, 2025)
This study examines the implementation of LOSIDA (Lodong Sisa Dapur), an integrated organic waste management system, at Muhammadiyah University of Sorong. The research employs a quantitative experimental approach, focusing on system design evaluation, composting process analysis, and end-product characterization. The LOSIDA system, constructed using 4-inch PVC pipes with strategic aeration holes, demonstrates effective conversion of household organic waste into quality compost over a three-month period. The integration of the composting system with planting media creates an efficient closed nutrient cycle, enabling direct utilization of decomposition products. Results indicate successful organic matter degradation with optimal C/N ratio management (25:1) and proper aeration control. The final compost exhibits desirable physical characteristics, including homogeneous crumbly texture and dark brown coloration, indicating proper humus content. This research validates LOSIDA as a practical solution for sustainable household organic waste management in urban areas.